Closure of Patent Foramen Ovale versus Medical Therapy after Cryptogenic Stroke: Meta-Analysis of Five Randomized Controlled Trials with 3440 Patients - Sá, Michel Pompeu Barros Oliveira (Braz J Cardiovasc Surg, 2018)
OBJECTIVE: We aimed to determine whether patent foramen ovale closure reduces the risk of stroke, also assessing some safety outcomes. INTRODUCTION: The clinical benefit of closing a patent foramen ovale after a cryptogenic stroke has been an open question for several decades, so that it is necessary to review the current state of published medical data in this regard. METHODS: MEDLINE, EMBASE, CENTRAL/CCTR, SciELO, LI-LACS, Google Scholar and reference lists of relevant articles were searched for randomized controlled trials that reported any of the following outcomes: stroke, death, major bleeding or atrial fibrillation. Five studies fulfilled our eligibility criteria and included 3440 patients (1829 for patent foramen ovale closure and 1611 for medical therapy). RESULTS: The risk ratio (RR) for stroke in the "device closure" group compared with the "medical therapy" showed a statistically significant difference between the groups, favouring the "device closure" group (RR 0.400; 95% CI 0.183-0.873, P=0.021). There was no statistically significant difference between the groups regarding the safety outcomes death and major bleeding, but we observed an increase in the risk of atrial fibrillation in the "device closure group (RR 4.000; 95% CI 2.262-7.092, P<0.001). We also observed that the larger the proportion of effective closure, the lower the risk of stroke. CONCLUSION: This meta-analysis found that stroke rates are lower with percutaneously implanted device closure than with medical therapy alone, being these rates modulated by the rates of effective closure.